Razón práctica y objetividad del derecho : el debate contemporáneo acerca de los principios jurídicos - Massini Correas, Carlos I. (Sapientia, 2008)
This article is a presentation of the different attempts to create new grounds for ethics and law. Since the Enlightenment, the legal foundations had to be objective while at the same time not based on the legal sources so far accepted. This work aims at giving a systematic view on the answers given to the problem of legal objectivity. It also expects to show the consequences that follow from each of those answers in the field of legal philosophy and the theory of law. The author goes about by elucidating the terms principle and objectivity within the realm of law and rights. He makes a portrait of the different theories and the aspects entailed in them. To conclude, the author presents his conclusions.